Long-term food insecurity, hunger and risky food acquisition practices: A cross-sectional study of food charity recipients in an Australian capital city - Pollard, Christina; Booth, S.; Jancey, Jonine; Mackintosh, B.; Pulker, Claire; Wright, Janine; Begley, Andrea; Imtiaz, Sabrah; Silic, Claire; Mukhtar, Aqif; Caraher, M.; Berg, J.; et al. (MDPI, 2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Inadequate social protection, stagnant wages, unemployment, and homelessness are associated with Australian household food insecurity. Little is known about the recipients of food charity and whether their needs are being met. This cross-sectional study of 101 food charity recipients in Perth, Western Australia, measured food security, weight status, sociodemographic characteristics and food acquisition practices. Seventy-nine percent were male, aged 21–79 years, 90% were unemployed, 87% received social assistance payments, and 38% were homeless. Ninety-one percent were food insecure, 80% with hunger, and 56% had gone a day or more without eating in the previous week. Fifty-seven percent had used food charity for ≥1 year, and, of those, 7.5 years was the mode. Charitable services were the main food source in the previous week, however 76% used multiple sources. Begging for money for food (36%), begging for food (32%), stealing food or beverages (34%), and taking food from bins (28%) was commonplace. The omnipresence and chronicity of food insecurity, reliance on social security payments, and risky food acquisition suggest that both the social protection and charitable food systems are failing. Urgent reforms are needed to address the determinants of food insecurity (e.g., increased social assistance payments, employment and housing support) and the adequacy, appropriateness and effectiveness of food charity.